Fasted and furious? Considerations on the use of fasting days in large carnivore husbandry - Kleinlugtenbelt, Cellina; Clauss, Marcus; Burkevica, Anita; De Cuyper, Annelies (Journal of Zoo and Aquarium Research, 2023)
Many large mammalian terrestrial carnivores do not hunt every day in their natural habitats, because given the right prey, they can gorge-feed more than their daily energy and nutrient requirements. At the same time, there is a tradition of exposing these species to one or several fasting days per week in zoos. In this study husbandry guidelines for large carnivores were surveyed, and feeding routines recorded in 44 European zoos. Husbandry guidelines did not suggest that fasting days should be preceded by gorge-feeding, and the most common practice observed at the zoos also did not include a gorge-feeding day prior to the fasting day. This raises the question why fasting days are implemented in zoo regimes in the first place. The observed practice of providing special enrichment on fasting days might stem from the impression that animals are not at ease when fasting after receiving a food portion basically corresponding to little more than their daily requirement on the day before, without a feeling of satiety related to gut distension. These current feeding regimes of zoo carnivores should be re-assessed. The combination of fasting days with preceding gorge-feeding, together with strenuous physical activity and cognitive challenges linked to the feeding event, might have the potential to mimic natural behaviours more closely than current practices. This should be investigated in future studies.